Optimization of Pineapple Leaf Fiber-Reinforced ABS Waste Filaments for FDM: Effect of Mesh Size and Volume Fraction - Wahyu Sipahutar; Azizul Fikri; Risa Nurin Baiti; Mhd Yasin Siregar; Faiza Armalia Putri (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
Acrylonitrile Butadiene Styrene (ABS) plastic waste presents significant potential for upcycling into environmentally friendly materials, particularly as feedstock for 3D printing filaments in Fused Deposition Modeling (FDM). This study investigates the influence of pineapple leaf fiber (PALF) reinforcement at two weight fractions (3% and 5%) and two mesh sizes (200 and 300) on the dimensional stability, printability, and mechanical properties of ABS waste-based composite filaments. Comprehensive evaluations were conducted, including filament diameter consistency, surface morphology, and uniaxial tensile testing. The 5% fiber content with 300-mesh PALF yielded the most stable filament diameter (average 1.73 mm, CV 2%), while the same formulation also achieved the highest ultimate tensile strength (UTS) of 8.873 MPa and elongation at break of 0.197%. Interestingly, the highest Young’s modulus (0.139 GPa) was observed in the 3%–300 mesh variant, although it exhibited more brittle behavior. Overall, the 5%–300 mesh formulation was identified as optimal, striking a favorable balance between tensile strength, flexibility, and dimensional consistency, thereby validating its suitability as a sustainable FDM filament derived from post-consumer ABS waste.